Hubungan Antara Konsep Diri dan Kematangan Emosi dengan Penyesuaian Diri Istri yang Tinggal Bersama Keluarga Suami - Nova Anissa; Agustin Handayani (Universitas Muria Kudus, 2012)
Adjustment to the wife in husband's family is one of the essential inmarital adjustment. The success of the wife in the process of adjustment to the husband's family will give a sense of satisfaction, happiness and stability in the lives of his wife and soul to create harmony, both the husband and the husband's family. Adjustment wife was itself influenced by the concept of self and emotional maturity. This study aims to determine empirically the relationship between self concept and emotional maturity with self-adjustment on wife who lives with husband's family.The population in this study is the wife in the RW. 03 GodongVillage, District Godong, District Grobogan with characteristics: living with husband's family, the marriage age is less than 5 years and the first marriage. The sampling method used is purposive sampling with sample size 60 people. Data analysis technique used is multiple regression analysis and partial correlation analysis.The results of regression analysis correlation coefficient valuesobtained Rx12y = 0.603, F = 16.247 with p = 0.000 (p smaller than 0.01) and coefficient of determination = 0.363, that it can be concluded there is a relationship between self concept and emotional maturity to self-adjustment wife who lived with family husband, the effective contribution of the variable self concept and emotional maturity to self-adjustment wife who lives with husband's family at 36.3%. The results obtained partial correlation analysis (1) correlation coefficient rx1y-2 = 0.362 with p = 0.005 (p smaller than 0.01), so that there are positive and highly significant relationship between self-concept and self-adjustment wife who lives with husband's family by controlling the emotional maturity, (2) the correlation coefficientrx2y-2 = 0.336 with p = 0.009 (p smaller than 0.01), so that there are positive and highly significant relationship between emotional maturity with self-adjustment wife who lives with husband's family with the concept of self-control.